2002
DOI: 10.1021/cm010794w
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Capped Ultrafine γ-Fe2O3Particles from Iron(III) Hydroxide Caprylate:  A Novel Starting Material for Readily Attainable Organosols

Abstract: The synthesis of capped γ-Fe 2 O 3 ultrafine particles from thermal treatment of iron(III) hydroxide caprylate in boiling tetraline with retention of the integrity of the caprylate units during the reaction process is reported. This novel material due to the organophilic mantle around the particle surfaces can be easily dissolved in organic solvents and thus the availability of stable magnetic organosols is straightforward. The formation of capped magnetic particles is accomplished only under anaerobic conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 25 publications
4
51
0
Order By: Relevance
“…First, our simple synthetic procedure has resulted in pure nanoscale mesoporous particles of g-Fe 2 O 3 , while most of the literature-reported work involved stabilizing the particles by dispersion into organic or inorganic matrices, [22±30] or by coating with relatively thick layer of organic additives. [31,32,49] Second, all studies that have been reported on the synthesis of pure g-Fe 2 O 3 involved extra steps such as the preparation of a-Fe 2 O 3 first followed by vaporization condensation to convert it to the g-phase, [38] or the preparation of Fe 3 O 4 first followed by oxidation to gFe 2 O 3 . [8,13] Direct precipitation in aqueous media under specific conditions has also resulted in g-Fe 2 O 3 , but this method is very sensitive to experimental conditions especially the pH of the solution which makes the formation of impurities very likely to occur.…”
Section: Resultsmentioning
confidence: 99%
“…First, our simple synthetic procedure has resulted in pure nanoscale mesoporous particles of g-Fe 2 O 3 , while most of the literature-reported work involved stabilizing the particles by dispersion into organic or inorganic matrices, [22±30] or by coating with relatively thick layer of organic additives. [31,32,49] Second, all studies that have been reported on the synthesis of pure g-Fe 2 O 3 involved extra steps such as the preparation of a-Fe 2 O 3 first followed by vaporization condensation to convert it to the g-phase, [38] or the preparation of Fe 3 O 4 first followed by oxidation to gFe 2 O 3 . [8,13] Direct precipitation in aqueous media under specific conditions has also resulted in g-Fe 2 O 3 , but this method is very sensitive to experimental conditions especially the pH of the solution which makes the formation of impurities very likely to occur.…”
Section: Resultsmentioning
confidence: 99%
“…For a particular system, the blocking temperature depends on the particle size, anisotropy energies, the time scale of the measuring technique and on the degree of the interparticle interactions. Since noninteracting systems have blocking temperature strongly dependent on the volume of individual particles [4,[17][18][19][20], the constant blocking temperature is likely to be associated with inter-particle dipolar and exchange interactions yielding a collective behaviour. Several models have been suggested to explain the magnetic behaviour of interacting systems based on dipolar and exchange interactions [3,21,22].…”
Section: Resultsmentioning
confidence: 99%
“…Diamagnetic materials are also used in the synthesis of inverse FFs. As of now, different metals (Fe, Co, Ni, Gd), metal nitrides such as iron nitride (Fe x N), metal oxides (Fe 3 [2,29,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] Metallic FFs based on mercury prepared by suspending alloy particles of FeÀB, FeÀCoÀB, FeÀNiÀB, and CoÀB have also been synthesized by the reduction of transition-metal ions in aqueous solutions using NaBH 4 in mercury. [42] Even though the choice of magnetic material is wide, its proper compatibility with the surfactant and carrier medium is essential for enhancing the suspension stability.…”
Section: Synthesis Of Ferrofluidsmentioning
confidence: 99%